CD44 facilitates adherence of Streptococcus equi subsp. zooepidemicus to LA-4 cells. (March 2019) - Fu, Qiang; Li, Wenwen; Li, Shun; Zhao, Xianjie; Xie, Honglin; Zhang, Xi; Li, Kangjian; Ma, Chunquan; Liu, Xiaohong
Abstract: Streptococcus equi subsp. zooepidemicus ( S. zooepidemicus ) causes a wide variety of infections in many species. CD44 is a transmembrane adhesion molecule, expressed by various cell types, which has been implicated in several infection processes. The aim of this study was to examine the role of CD44 in S. zooepidemicus adherence to LA-4 cells (mouse lung adenoma). Dose-dependent adhesion with LA-4 may be effectively studied by flow cytometry. Adherence of S. zooepidemicus is reduced after treatment of cells with anti-CD44 antibody. Treatment of S. zooepidemicus with recombinant CD44 significantly reduced bacteria adherence. In addition, CD44 can directly bind to wild-type S. zooepidemicus, while the binding was decreased in the capsule deletion isogenic mutant. These data suggest that CD44 facilitates adherence of S. zooepidemicus to LA-4 cells. Highlights: Adherence of S. zooepidemicus is reduced after treatment of cells with CD44 antibody. Treatment of S. zooepidemicus with recombinant CD44 significantly reduced bacteria adherence. CD44 facilitates adherence of S. zooepidemicus to LA-4 cells.